ANALISIS PENGEMBANGAN BAHASA MELALUI KEGIATAN PENGENALAN KARTU HURUF DI TK SAMUDERA PADANG - Dwi Mutia Chan; Najmi Hayati; Zuraida Chairani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
This study aims to find out language development through letter card recognition activities at TK Samudera Padang. The method used is descriptive with qualitative approach. Results research shows that the medium of letter cards used by teachers has not been fully qualified in the selection of language learning media. Implementation children's letter recognition language learning looks actively learning to recognize letters, letter card media provides convenience for children to recognize shapes and sounds letter. Success rate of alphabetic letter recognition learning with media letter cards on group B1 children at Samudera Padang. If presented were 73.4% of children familiar with alphabetic letters and 28.4% of children alphabetic letters.Based on the results of the research that has been presented, the researchers presented some suggestions, namely in developing early childhood language through the application of letter card media should teachers involve more children in question and answer activities, as well as bring the child to a certain place or object that can increase the child's knowledge and insight, improving the development of children's language through the application of letter card media should be adjusted to the level of child development and carried out in an integrated manner.